SERCA2a superinhibition by human phospholamban triggers electrical and structural remodeling in mouse hearts - Wang, H. S.; Arvanitis, DA; Dong, M.; Niklewski, P. J.; Zhao, W.; Lam, C. K.; Kranias, EG; Sanoudou, D. (Physiol GenomicsPhysiol GenomicsPhysiol Genomics, 2011)
Phospholamban (PLN), the reversible inhibitor of the sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA2a), is a key regulator of myocyte Ca(2+) cycling with a significant role in heart failure. We previously showed that the single amino acid difference between human and mouse PLN results in increased inhibition of Ca(2+) cycling and cardiac remodeling and attenuated stress responses in transgenic mice expressing the human PLN (hPLN) in the null background. Here we dissect the molecular and electrophysiological processes triggered by the superinhibitory hPLN in the mouse. Using a multidisciplinary approach, we performed global gene expression analysis, electrophysiology, and mathematical simulations on hPLN mice. We identified significant changes in a series of Na(+) and K(+) homeostasis genes/proteins (including Kcnd2, Scn9a, Slc8a1) and ionic conductance (including L-type Ca(2+) current, Na(+)/Ca(2+) exchanger, transient outward K(+) current). Simulation analysis suggests that this electrical remodeling has a critical role in rescuing cardiac function by improving sarcoplasmic reticulum Ca(2+) load and overall Ca(2+) dynamics. Furthermore, multiple structural and transcription factor gene expression changes indicate an ongoing structural remodeling process, favoring hypertrophy and myogenesis while suppressing apoptosis and progression to heart failure. Our findings expand current understanding of the hPLN function and provide additional insights into the downstream implications of SERCA2a superinhibition in the mammalian heart.
Keywords: Animals; Calcium-Binding Proteins/genetics/*metabolism; Calcium/metabolism; Computational Biology; Electrophysiology; Humans; Immunoblotting; In Vitro Techniques; inhibitors/*metabolism; Male; Mice; Models, Theoretical; Myocytes, Cardiac/*metabolism; Oligonucleotide Array Sequence Analysis; Sarcoplasmic Reticulum Calcium-Transporting ATPases/antagonists &